STIMULASI OSTEOBLAS OLEH HIDROKSIAPATIT SEBAGAI MATERIAL BONE GRAFT PADA PROSES PENYEMBUHAN TULANG - Hengky Bowo Ardhiyanto (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
Bone has natural repair mechanism, but there are some critical sized defects which will not allow the tissues to regenerate themselves. The clinical success of bone graft is dependent on the formation of an intimate contact between the material surface and mineralized tissue. Osteoblast attachment, proliferation and differentiation must be optimized in order for the mineralization, necessary for this intimate contact to occur. One of the bioceramics are frequently used in biomedical applications as a bone graft is a hydroxyapatite. Hydroxyapatite is a popular bone substitute material. The composition of hydroxyapatite crystals have an overview identical to hydroxyapatite in bone. This material is biocompatible, osteoinductive and osteoconductive, thus hydroxyapatite can be a medium for osteoblast to growth and improve the bone healing process.